2019
DOI: 10.1038/s41598-019-52352-w
|View full text |Cite
|
Sign up to set email alerts
|

Early evening light mitigates sleep compromising physiological and alerting responses to subsequent late evening light

Abstract: The widespread use of electric light and electronic devices has resulted in an excessive exposure to light during the late-evening and at night. This late light exposure acutely suppresses melatonin and sleepiness and delays the circadian clock. Here we investigate whether the acute effects of late-evening light exposure on our physiology and sleepiness are reduced when this light exposure is preceded by early evening bright light. Twelve healthy young females were included in a randomised crossover study. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 59 publications
1
36
0
Order By: Relevance
“…If the aim is to minimize melanopic light exposures, the lighting used at night for navigation and perceptions of safety should be restricted to lower M/P ratios. Increased daytime light exposures can reduce the adverse effects of evening light (39)(40)(41)(42)(43)(44)(45)(46), and daytime light exposure may be as important as avoiding bright light before bedtime. During the day, indoor electric lighting could reproduce the melanopic light exposures (and other facets) of the outdoor environment, although this entails greatly increased indoor illuminances.…”
mentioning
confidence: 99%
“…If the aim is to minimize melanopic light exposures, the lighting used at night for navigation and perceptions of safety should be restricted to lower M/P ratios. Increased daytime light exposures can reduce the adverse effects of evening light (39)(40)(41)(42)(43)(44)(45)(46), and daytime light exposure may be as important as avoiding bright light before bedtime. During the day, indoor electric lighting could reproduce the melanopic light exposures (and other facets) of the outdoor environment, although this entails greatly increased indoor illuminances.…”
mentioning
confidence: 99%
“…Taking a closer look at the limit cycle model in an attempt to explain the resulting light levels, we see that increasing the light in the early afternoon increases the amplitude of the van der Pol oscillator, as captured by Equations (1) and (2). Interestingly, we did see experimental studies [ 37 , 38 ] that investigate the effects of late evening exposure on physiology and sleepiness, specifically when this light exposure is preceded by early evening light. Yet, seeing also the experimental studies in [ 39 ] that showed that high-amplitude rhythms introduce larger phase-shifting responses, we hesitate to claim that our model explains their findings via amplitude shifts, but recommend further study.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, acute melatonin suppression by light may not be a suitable proxy for other physiological responses, such as circadian phase shifting and alertness ( 37 , 70 ). The human circadian system adapts to prior light exposure ( 71 ), light exposure earlier in the day affects the biological potency of light later in the day ( 72 75 ), extended periods under dim light may negatively impact subsequent sleep ( 76 ), and there is considerable interindividual variability in the response to evening light ( 77 ). Collectively, these findings suggest nuance in the human circadian response to light, raising questions about the veracity of numerical design targets for circadian lighting design.…”
Section: Foundational Considerationsmentioning
confidence: 99%